Strategi Lembaga Penyiaran Publik TVRI Sumatera Barat Dalam Mempertahankan Eksistensi Program Siaran Lokal (Studi Pada Program Acara Ngobrol Penuh Inspirasi) - Indri Eka Putri; Zike Martha (CV. ITTC INDONESIA, 2026)
This study discusses the strategy of the Public Broadcasting Institution TVRI West Sumatra in maintaining the existence of local broadcast programs, particularly the Ngobrol Penuh Inspirasi program. The research problems focus on program planning, variations in program presentation, and the strategies used by TVRI West Sumatra to maintain the continuity of the program as a local broadcast. This research applies a descriptive qualitative approach using primary data from research informants and secondary data from reference books, documents, and literature studies. Data were collected through observation, interviews, documentation, and literature review. Informants were selected purposively based on their capacity, involvement, and willingness to provide information about program management. The data were analyzed through data reduction, data presentation, and conclusion drawing, while data validity was examined through source triangulation. The results show that TVRI West Sumatra's planning process is carried out through technical preparation, topic selection, and selection of program contributors. The presentation variation of Ngobrol Penuh Inspirasi is developed through inspirational concepts and dialogical interaction between hosts and resource persons. The strategy to maintain program existence is implemented through professional human resources, inspiring content packaging, institutional partnerships, program socialization through advertising spots, and the use of social media.